2016
DOI: 10.15376/biores.11.3.6880-6895
|View full text |Cite
|
Sign up to set email alerts
|

4-Methylcatechol-treated Jute-Bamboo Hybrid Composites: Effects of pH on Thermo-Mechanical and Morphological Properties

Abstract: Hybrid composites were fabricated with 4-methylcatechol-treated jute and bamboo fiber at different pH levels. The effects of different pH levels on the thermal, mechanical, and morphological properties of jute-bamboo hybrid composites were investigated. Fabricated hybrid composites were characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), dynamic mechanical thermal analysis (DMTA), and adhesion test analysis. Additionally, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…. Based on previous studies, it has been established that there is no significant degradation of hybrid composite up to 300°C . Above this temperature, the decomposition occurs and thermal stability decreased.…”
Section: Resultsmentioning
confidence: 99%
“…. Based on previous studies, it has been established that there is no significant degradation of hybrid composite up to 300°C . Above this temperature, the decomposition occurs and thermal stability decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found that there is no degradation of jute-bamboo hybrid composite up to 300 ∘ C [36]. Above this temperature, the decomposition takes place and thermal stability decreased.…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 86%
“…3 (c) showed a smooth and uniform surface for the 50:50 FA-co-EHMA-HNC WPNCs ( Rahman et al, 2015 ). A strong interfacial bond between the wood fiber and FA-co-EHMA-HNC was formed, which reduced the amount of hydroxyl groups in the wood fiber ( Liew et al, 2016 ). The surface in Fig.…”
Section: Resultsmentioning
confidence: 99%